2020
DOI: 10.3390/su12104331
|View full text |Cite
|
Sign up to set email alerts
|

Varying Effects of Urban Tree Canopies on Residential Property Values across Neighborhoods

Abstract: As more land area than ever is covered with impermeable surfaces causing problems in the environment, urban trees are effective not only in mitigating environmental problems in the built environment and reducing buildings’ energy use, but also in increasing social and economic benefits. However, the benefits urban trees provide are not evenly distributed but rather disproportionately distributed in high-income neighborhoods. The purpose of this study is to estimate the varying effects of urban trees based on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…At the residential property scale, tree canopy coverage was reported to have a positive effect on residential property values [ 16 , 29 , [49] , [50] , [51] ], particularly for middle-to high-income homes with large lots [ 52 ]. At the neighborhood public space scale, several studies reported a positive effect of large forest/tree canopy coverage/green vegetation cover within a radius buffer of 20 m–400 m (e.g., Refs.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…At the residential property scale, tree canopy coverage was reported to have a positive effect on residential property values [ 16 , 29 , [49] , [50] , [51] ], particularly for middle-to high-income homes with large lots [ 52 ]. At the neighborhood public space scale, several studies reported a positive effect of large forest/tree canopy coverage/green vegetation cover within a radius buffer of 20 m–400 m (e.g., Refs.…”
Section: Resultsmentioning
confidence: 99%
“…Tree canopy coverage within a residential property was reported to have a negative effect on residential property values in the majority of cases [ 24 , 25 , 42 , 50 , 65 , 66 ], particularly in low-income neighborhoods [ 16 , 52 ]. A few studies found tree cover within residential properties to have a non-significant effect on housing prices [ 34 , 53 , 67 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The paper by Youngme Seo entitled "Varying Effects of Urban Tree Canopies on Residential Property Values across Neighborhoods, social and economic benefits" [4] utilizes spatial models to empirically evaluate the impact of Urban Tree Canopy (UTC) on residential property values in the housing market. The Author elaborates a dataset that includes 24,203 singlefamily residential sales from 2007 to 2015 in the city of Des Moines (Iowa).…”
Section: Sustainable Real Estatementioning
confidence: 99%